ChemInform Abstract: Catalytic Desulfitative Homocoupling of Sodium Arylsulfinates in Water Using PdCl2 as the Recyclable Catalyst and O2 as the Terminal Oxidant. Issue 16 (28th March 2013) - Rao, Bin; Zhang, Weixi; Hu, Lan; Luo, Meiming
Abstract The applied catalytic system can be recycled several times by just reusing the already used aqueous phase without recharging of catalyst and water.